2020
DOI: 10.1186/s12912-020-00421-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive nursing practices in working with mothers to care for hospitalised children at a district hospital in KwaZulu-Natal, South Africa: a descriptive observational study

Abstract: Background: The presence of family members and their active involvement in caring for hospitalised children is an established practice in many African paediatric settings, with family members often regarded as a resource. This aspect of African paediatric nursing practice lacks formal expression or a clear conceptual basis, and difficulties arise when applying concepts of family involvement originating from the culturally distinct practice environments of higher resourced settings including Europe and America.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Involvement of mothers in the care of the child forges relationships between the mother and the nurse, and encourages the family of the child to have a sense of trust in the nurses working closely with the child and the mother (Salmani, Abbaszadeh & Rassouli 2014). Highquality African nursing practices have been described, where mothers were expected by nurses to become quickly competent at managing the hospitalised child's health needs, and participate in care such as observing the child's condition, tube feeding, prescribed physiotherapy exercises, providing a reassuring presence for the child during procedures and dressing changes and assisting with giving medication (North et al 2020). This suggests that it is feasible to involve mothers in this aspect of caregiving and that nurses can do so with confidence, supported by evidence, as part of strategies to reduce medication errors and improve safety for children in hospital.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of mothers in the care of the child forges relationships between the mother and the nurse, and encourages the family of the child to have a sense of trust in the nurses working closely with the child and the mother (Salmani, Abbaszadeh & Rassouli 2014). Highquality African nursing practices have been described, where mothers were expected by nurses to become quickly competent at managing the hospitalised child's health needs, and participate in care such as observing the child's condition, tube feeding, prescribed physiotherapy exercises, providing a reassuring presence for the child during procedures and dressing changes and assisting with giving medication (North et al 2020). This suggests that it is feasible to involve mothers in this aspect of caregiving and that nurses can do so with confidence, supported by evidence, as part of strategies to reduce medication errors and improve safety for children in hospital.…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
“…A distinctive feature of many African paediatric wards is the presence of a caregiver (often the mother) who is admitted with the child (North et al 2020). It has been reported that caregivers of admitted children assist with a variety of daily activities including bathing of children, feeding and even monitoring of medication for the children (Hoffman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital, familial involvement maximises limited resources, decreases staff burnout and improves patient safety (Micalizzi et al 2015 ). Families desire to be involved in their child’s hospital care (Bisogni et al 2015 ; Micalizzi et al 2015 ; North et al 2020 ) and the intentional involvement of mothers and caregivers holds promise to promote sleep in hospitals by capitalising on nurse’s relational strengths (Keys & Benzies 2018 ). For the child and family, the benefits may extend beyond hospital discharge (Erondu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…End users of the guideline were envisaged to be bedside nurses in conjunction with members of the wider healthcare team and in collaboration with the child’s bedside carer (most often the child’s mother) and staff. Involving mothers was crucial to the continuity of sleep for the child as sleep practices are known to vary by culture (National Research Council & Institute of Medicine 2000 ) and hospital (North et al 2020 ).…”
Section: Research Methods and Designmentioning
confidence: 99%
“…Each table was set up to explore one of eight care outcome domains. Two people (a facilitator and a summariser) were *In our work (North, Leonard, Bonaconsa, Duma, Coetzee, 2020) we have observed that the majority of children in hospital are accompanied by a female relative widely referred to as the child's mother. Mother is therefore used to refer to any woman accompanying and caring for a child in hospital, whether or not they are the child's biological mother or a grandmother, aunt, older sister or foster mother.…”
Section: Processes To Develop Nursing Care Outcome Statementsmentioning
confidence: 99%